2004
DOI: 10.1248/cpb.52.858
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Superoxide Anion Generation by Neutrophils from Viscum articulactum

Abstract: The genus Viscum, plants of the Loranthaceae family, are photosynthetic shrubby, hemiparasites on the tree branches of the Moraceae, Theaceae, Ranunculaceae, Rutaceae, Rosaceae and Leguminosae families. In clinical use, Lorthanthus genus plants could be replaced by Viscum genus plants, but they belong to different genera of Loranthaceae. Viscum articulatum BURM. has commonly been used in Chinese medicine as a curative for a number of ailments such as hemorrhage, pleurisy, gout, heart disease, epilepsy, arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…These data showed that compound 1 had the 1,3-diphenylpropane skeleton. In addition, d C 154.7 (C-6Ј), 151.7 (C-2Ј), 133.9 (C-3Ј), 146.6 (C-3Љ) and methoxyl protons d H 3.74, 3.82, 3.85, 3.88 also showed 3 J correlations, respectively. Above these data, the nucleus of compound 1 could be determined.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…These data showed that compound 1 had the 1,3-diphenylpropane skeleton. In addition, d C 154.7 (C-6Ј), 151.7 (C-2Ј), 133.9 (C-3Ј), 146.6 (C-3Љ) and methoxyl protons d H 3.74, 3.82, 3.85, 3.88 also showed 3 J correlations, respectively. Above these data, the nucleus of compound 1 could be determined.…”
mentioning
confidence: 93%
“…The known compounds, (2S)-5,7,3Ј,4Ј-tetrahydroxyfla- 3) 5,7-dihydroxychromone (14), 10) 5-hydroxychromone-7-O-glucoside (15), 10) methyl-3-O-feruloylquinate (16), 11) 4-O-cinnamoylquinic acid (17), 3) oleanolic acid (18), 3) betulinic acid (19), 12) b-amyrin acetate (20), 3) lupeol (21), 13) b-sitostenone (22), 14) stigmasterol (23)ϩb-sitosterol (24) mixtures, 15) 15) cinnamic acid (27), 16) coumaric acid (28), 15) ferulic acid (29), 15) caffeic acid (30), 15) 4-hydroxybenzaldehyde (31), 3) 4-hydroxybenzoic acid (32), 3) vanillin (33), 3) vanillic acid (34), 17) protocatechuic acid (35), 3) syringaldehyde (36), 17) acetovanillone (37), 18) 2,6-dimethoxy-p-benzoquinone (38), 19) 2-deoxyepi-inositol (39), 3) thymine (40) 20) and uracil (41) 21) were also isolated and identified by comparison of their spectral data with corresponding literature values.…”
mentioning
confidence: 99%
“…The methanolic extract of V. cinerea is known to possess triterpenes 33 , sesquiterpenes 34 , flavonoids, and phenylpropanoids 14 . Immunological activities of terpenes and flavonoids found in several plants have been reported [35][36][37] . Some sesquiterpenes, especially sesquiterpenes lactones, show a wide range of biological activities, such as anti-bacterial, anti-tumour, anti-virus, cytotoxic, and immune inhibition 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Its UV absorption bands at 330 (sh) and 284 nm indicated the presence of a flavanone skeleton. 20 Its IR absorptions at 3424 and 1648 cm −1 inferred the hydroxyl and carbonyl groups, respectively. The 1 H NMR spectrum of 1 (Table 1) showed the presence of three mutually coupled protons at δ C NMR spectra (Table 1) also showed 1 to be a flavanone diglycoside possessing a furanosyl and a pyranosyl moiety.…”
mentioning
confidence: 99%
“…The glucose moiety was determined to have a β-configuration at H-1'' due to a large coupling constant for the anomeric proton of the sugar unit at δ H 5.62 (1H, d, J = 7.5 Hz), 20 and the apiose unit was also determined to have a β-configuration at C-1''' due to the chemical shift of its anomeric carbon signal in the 13 C NMR at δ C 110.9. 21,22 Comparison of the 13 C NMR spectra of 1 with those of (2S)-pinocembrin 7-O-[β-D-apiosyl(1→2)]-β-Dglucoside revealed they were very similar, except for the glucose C-6'' signal in 1 was downfield from δ C 61.0 to 68.5, suggesting that the interglycosyl linkage is apiosyl-(1→6)-glucose, 20,23 which was confirmed by the presence of the HMBC correlation between H-1''' and C-6'' ( Figure 2). The glycosidation position was further determined by the presence of the three-bond HMBC correlation between the glucosyl anomeric proton H-1'' and C-7 of ring A.…”
mentioning
confidence: 99%